2011
DOI: 10.1590/s1809-48722011000400013
|View full text |Cite
|
Sign up to set email alerts
|

Potenciais evocados auditivos de longa latência e processamento auditivo central em crianças com alterações de leitura e escrita: dados preliminares

Abstract: Summary Introduction:?Presently, it is admitted that individuals with reading and writing alterations may present delay in the development of listening skills, which may interfere in the learning process. The assessment of the listening skills can occur in a behavioral way, through central auditory processing (CAP) tests, or by electrophysiological assessment highlighting the long latency auditory evoked potentials (LLAEP). The use of the LLAEP as a means of complementary assessment of individuals with readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 14 publications
2
38
0
20
Order By: Relevance
“…Short latency potentials analyze the electrophysiological activity of the auditory system from the inner ear to the upper brainstem; the middle latency potentials analyze the potentials originated in the primary auditory cortex area, through thalamocortical and reticular formation, and the long latency potentials assess the electrophysiological activity from the thalamus to the auditory cortex and association areas. The electrophysiological study of hearing includes: brainstem auditory evoked potentials (BAEP), middle latency auditory evoked potentials (MLAEP) and the P300, respectively (12)(13)(14) . Thus, the auditory processing assessment is relevant to determine and qualify auditory disorders that might influence, in a negative way, aspects of communication such as language, speech, reading and writing, besides other mental functions such as attention, memory and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Short latency potentials analyze the electrophysiological activity of the auditory system from the inner ear to the upper brainstem; the middle latency potentials analyze the potentials originated in the primary auditory cortex area, through thalamocortical and reticular formation, and the long latency potentials assess the electrophysiological activity from the thalamus to the auditory cortex and association areas. The electrophysiological study of hearing includes: brainstem auditory evoked potentials (BAEP), middle latency auditory evoked potentials (MLAEP) and the P300, respectively (12)(13)(14) . Thus, the auditory processing assessment is relevant to determine and qualify auditory disorders that might influence, in a negative way, aspects of communication such as language, speech, reading and writing, besides other mental functions such as attention, memory and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Our study corroborates the aforementioned study, as there was no significant difference for the finding as to latency. In the literature there was also the rare stimulus counting in two ways namely: counting mentally 27 , counting mentally and raising the hand 21,26,28 to hear it and after, count aloud 21,29 .…”
Section: Resultsmentioning
confidence: 99%
“…A study developed with 18 subjects of similar age, of which eight had temporal lobe epilepsy and ten without cortical damage, it was observed that individuals with epilepsy had more deficits in auditory Figure 1 presents the publications [25][26][27][28][29][30][31][32][33][34][35] It was observed that, in most studies of individuals who had speech pathology, the temporal ordering ability was impaired, and FPT was the test most frequently used to assess this ability.…”
Section: Clinical Applications Of Frequency Patterns and Duration Patmentioning
confidence: 99%
“…Most studies used only behavioral tests to assess temporal ordering, there were only two studies that associated behavioral and electrophysiological tests 3,35 . This finding suggests new research perspectives that associate behavioral and electrophysiological measures in the assessment of temporal ordering skills.…”
Section: Figure 1 -Studies Of Literature Describing the Applications mentioning
confidence: 99%